Japanese government research grants for Kampo medicine: an overview of 10 years (1997–2017) - Min Kyung Hyun; Hong Yeoul Yoon; Tetsuhiro Yoshino; Min Jung Park (Integrative Medicine Research)
Background: Japan has its own traditional medicine called Kampo medicine, but it is relatively unknown compared to traditional Chinese medicine. Therefore, this study examined the current status of the research related to Kampo medicine supported by Japanese government research grants (JGRG). Methods: Three databases were searched on October 2019: National Institute of Public Health, Grant-in-Aid for Scientific Research and Japan Agency for Medical Research and Development. The search keywords were Kampo medicine, acupuncture, integrative medicine, oriental medicine, and traditional medicine. The final research that satisfied the inclusion criteria were selected and analyzed. Results: After a comprehensive search of the three databases and removing any duplication research, 2,246 JGRG (985 new proposals) that met the inclusion criteria were selected. The number and amount of JGRG on Kampo medicine have been increasing steadily. The basic research conducted by academic research institutes was mainstream, and the proportion of development research of new Kampo medical technology was low. Most research were non-clinical research and 21 % were clinical research. The largest research institute was the Toyama University and there were many non-clinical, cancer, and Juzentaihoto (Japanese herbal medicine) research. The Japanese government grants were funded relatively evenly without bias to specific fields or institutions. Conclusions: The Japanese government research grants from 1973 to 2017 indicate that research on Kampo medicine which barely had any interest previously, was revived in the 2000s. In particular, it increased sharply in the 2010s, and the research fields were relatively diverse. Keywords: Kampo medicine, National institute of public health (NIPH), Grant-in-Aid for scientific research (KAKEN), Japan agency for medical research and development (AMED)